Laju Korosi Logam Baja Karbon Rendah di Larutan Garam pada Berbagai Konsentrasi Inhibitor Korosi dari Ekstrak Daun Pepaya: Low Carbon Steel Metal Corrosion Rate in Salt Solution at Various Concentrations of Corrosion Inhibitor from Papaya Leaf Extract - Ninik Lintang Edi Wahyuni; Rony Pasonang Sihombing; Nurcahyo; Agustinus Ngatin; Yunus Tonapa Sarungu; Alfiana Adhitasari; Bambang Soeswanto; Emma Hermawati Muhari; retno indarti (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
Papaya leaf extract could be used as an organic corrosion inhibitor. Corrosion inhibitors were used as a method to reduce corrosion rate. The most corrosive environment was the marine environment. The purpose of this study was to determine the best concentration of papaya (Carica papaya) leaf extract inhibitor which could reduce the corrosion rate of low carbon steel in a 3.56% NaCl solution environment. The maceration process was carried out for 24 hours with 70% ethanol solvent with a solute:solvent ratio of 1:8 (w/v) at room temperature. Inhibitor extracts were analyzed qualitatively with the phytochemical method. The addition of FeCl3 was carried out on the inhibitor extract from papaya leaves. The color change occurred from blackish brown to greenish black which indicated the presence of tannin compounds in the papaya leaf extract. Corrosion testing was carried out with hot stream temperature setting at 45â°C to 55â°C and concentrations of inhibitor extracts at 300, 600, and 900 ppm. The test was conducted for 36 hours with a span of metal mass every 6 hours. Corrosion rate calculation is done by weight loss method. The results showed that papaya leaf extract inhibitors positive contained corrosion inhibitor and could reduce the corrosion rate in 3.56% NaCl solution. The corrosion rate without inhibitor is 1.023 mmpy. Corrosion rates with inhibitor concentrations of 300, 600, and 900 ppm were 0.755, 0.585, and 0.438 mmpy, respectively.